2019
DOI: 10.1038/s41467-019-11091-2
|View full text |Cite
|
Sign up to set email alerts
|

Dual stem cell therapy synergistically improves cardiac function and vascular regeneration following myocardial infarction

Abstract: Since both myocardium and vasculature in the heart are excessively damaged following myocardial infarction (MI), therapeutic strategies for treating MI hearts should concurrently target both so as to achieve true cardiac repair. Here we demonstrate a concomitant method that exploits the advantages of cardiomyocytes derived from human induced pluripotent stem cells (hiPSC-CMs) and human mesenchymal stem cell-loaded patch (hMSC-PA) to amplify cardiac repair in a rat MI model. Epicardially implanted hMSC-PA provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
132
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 174 publications
(138 citation statements)
references
References 37 publications
6
132
0
Order By: Relevance
“…7) [15]. Although it is still unclear whether engraftment or retention of transplanted cells is necessary for their cardiac beneficial effects, there is evidence linking the beneficial effects to better retention[38, 39]. Our results may help assuage the concern as to whether sufficient numbers of cells delivered with this method are retained in the heart.…”
Section: Discussionmentioning
confidence: 88%
“…7) [15]. Although it is still unclear whether engraftment or retention of transplanted cells is necessary for their cardiac beneficial effects, there is evidence linking the beneficial effects to better retention[38, 39]. Our results may help assuage the concern as to whether sufficient numbers of cells delivered with this method are retained in the heart.…”
Section: Discussionmentioning
confidence: 88%
“…Our present study showed that the engraftment and survival of MSCs in the peri-infarct myocardium were significantly increased with the APN treatment, accompanied with markedly improved cardiac function and decreased infarct size at 4-week after AMI. Compared with the genetic [32][33][34] and nongenetic modifications [35,36] In addition, the present study revealed that the remarkable beneficial effects of APN on MSCs survival and the following cardiac repairs were mediated by the activation of AMPK, which correlates well with our in vitro study that AMPK mediated the inhibitory effects of APN on the apoptosis of MSCs [18]. The activation of AMPK by APN is critical in cellular responses to metabolic stress involving energy generation and consumption [19,[41][42][43], thus mediating the protective effects of APN on the survival of MSCs [18,29] Furthermore, the present study has found that the cellular mechanisms underlying the striking therapeutic effects are mainly associated with anti-inflammation, anti-apoptosis activity, and enhancement of arteriogenesis and angiogenesis by synergism of APN and MSC transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…The subsequent phase is the proliferation and healing process, which involves the secretion of many proliferative or prosurvival cell factors, including transforming growth factor-β and interleukin-10, which promote ventricular remodeling. Several data have shown that inflammatory modulation is crucial for the recovery of cardiac function after the cell sheet transplantation in MI, and cell sheet can attenuate the inflammation [94] and enhance the expression levels of anti-inflammatory-related genes [95]. However, recent research suggests that the functional benefit of stem cell therapy is from an acute inflammatory-based wound healing response [14].…”
Section: Regulation Of Inflammationmentioning
confidence: 99%